University public transportation logistics service quality and student satisfaction: empirical evidence from Thailand - Raksmey Sann; Saharat Siripipattaworn (Cogent Business & Management, 2024)
Although students around campuses mostly rely on university public transportation (i.e. shuttle buses), studies on how university public transportation logistics service quality impacts student satisfaction are limited. Hence, this study investigates the university public transportation logistics service quality attributes that affect student satisfaction. Data obtained from 202 valid questionnaires completed by students who frequently use shuttle services were analyzed using partial least square structural equation modeling with the assistance of the statistical package for social sciences V. 27 and smart partial least squares 4.0. The results show that the university public transportation logistics service quality attributes of empathy, reliability, and timeliness significantly influenced student satisfaction. Specifically, reliability is most important when it comes to university public transportation logistics service quality, considering that transportation services should be safe and efficient. This suggests that the university public transportation logistics service quality is important for student satisfaction and should not be ignored. To the best of our knowledge, this is the first attempt at understanding the effects of university public transportation logistics service quality attributes on student satisfaction with university public transportation in Thailand.
Keywords: L83; M100; M160; Z320; 650; Logistics service quality; university public transportation; student satisfaction; empathy; perceived value; timeliness; reliability